2018
DOI: 10.1017/cem.2018.367
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the French version of the 4AT for screening the elderly for delirium in the emergency department

Abstract: CLINICIAN'S CAPSULE What is known about the topic? Delirium is frequent in older inpatients but often goes undetected. A short tool, the 4 A's Test (4AT), was created and validated for the detection of delirium. What did this study ask? This study compared the performance of the French version of the 4AT (4AT-F) with the Confusion Assessment Method (CAM) for the screening of delirium. What did this study find? The 4AT-F was a fast and reliable screening tool for delirium in the emergency department (ED). Why d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 25 publications
2
38
0
4
Order By: Relevance
“…Among them, we excluded 57 studies, 2 of which were validation studies of the 4AT using the same dataset with already included studies [ 23 , 24 ]. As a result, a total of 13 articles that met the inclusion criteria were finally identified in our systematic review [ 10 , 11 , 12 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, we excluded 57 studies, 2 of which were validation studies of the 4AT using the same dataset with already included studies [ 23 , 24 ]. As a result, a total of 13 articles that met the inclusion criteria were finally identified in our systematic review [ 10 , 11 , 12 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were evaluated to have a low risk of bias in the domain of “patient selection” except for two studies; one used a case-control design [ 12 ], which was categorized as unclear risk of bias, the other, which did not report clear inclusion and exclusion criteria [ 10 ], was classified as having a high risk of bias in that domain. Two studies [ 26 , 28 ] were considered to have a high risk of bias in both domains of “index test” and “reference standard test” because these studies used the same tester for two tests without blinding. One study [ 12 ] was also assigned as having a high risk of bias for the “reference standard test” domain for having no sufficient information provided in terms of whether the tester was qualified and whether there was blinding in terms of the index test.…”
Section: Resultsmentioning
confidence: 99%
“…The 4AT has been validated among older populations in many languages and in various clinical settings: furthermore it has been implemented across a number of medical specialties [25][26][27][28][29]. Bellelli et al [25] found the Italian version had a sensitivity of 89.7% and specificity 84.1% for screening delirium, while Hendry et al [26], in a UK study, showed that the 4AT diagnosed delirium with a sensitivity and specificity of 86.7% and 69.5% respectively.…”
Section: Los Increased By Three and Six Days For Patients With 4at Smentioning
confidence: 99%
“…A study by De et al in Australia [28], with about 40% of patients from a non-English speaking background (NESB), showed a sensitivity of 87-91% regardless of probable dementia or NESB, and an overall specificity of 80% that was somewhat worse (71%) for probable dementia and NESB patients [28]. Finally, Gagné at al [29] evaluated a French version of 4AT in four Canadian emergency departments with 84% sensitivity and 74% specificity for delirium.…”
Section: Los Increased By Three and Six Days For Patients With 4at Smentioning
confidence: 99%
“…8 Gagne et al evaluated the use of the 4AT-F as a screening tool for cognitive impairment in functionally semi-independent and independent patients age 65 years and older who were in the ED for a minimum of 8 hours, admitted or waiting to be admitted to the hospital. 9 They reported a sensitivity of 84% (95% confidence interval [CI]: 76-93) and a specificity of 74% (95% CI: 70-78) when compared with the Confusion Assessment Method (CAM) administered by a research assistant. There are only two other tools, the Recognizing Acute Delirium As part of your Routine (RADAR) and the CAM-ICU, that have been reported in the French-speaking population; 10 the 4AT-French is the only version that has been explicitly validated in a French-speaking, older, ED cohort.…”
Section: Introductionmentioning
confidence: 99%